Early alterations of the neuronal network processing whisker‐related sensory signal during absence epileptogenesis. Issue 2 (16th December 2021) - Laghouati, Emel; Studer, Florian; Depaulis, Antoine; Guillemain, Isabelle
Abstract: Objective: Epileptogenesis is the particular process during which the epileptic network builds up progressively before the onset of the first seizures. Whether physiological functions are impacted by this development of epilepsy remains unclear. To explore this question, we used Genetic Absence Epilepsy Rats From Strasbourg (GAERS), in which spike‐and‐wave discharges are initiated in the whisker primary somatosensory cortex (wS1) and first occur during cortical maturation. We studied the development of both the epileptic and the physiological wS1 circuits during cortical maturation to understand the interactions between them and the consequences for the animals' behavior. Methods: In sedated and immobilized rat pups, we recorded in vivo epileptic and whisker sensory evoked activities across the wS1 and thalamus using multicontact electrodes. We compared sensory evoked potentials based on current source density analysis. We then analyzed the multiunit activities evoked by whisker stimulation in GAERS and control rats. Finally, we evaluated behavioral performance dependent on the functionality of the wS1 cortex using the gap‐crossing task. Results: We showed that the epileptic circuit changed during the epileptogenesis period in GAERS, by involving different cortical layers of wS1. Neuronal activities evoked by whisker stimulation were reduced in the wS1 cortex at P15 and P30 in GAERS but increased in the ventral posteromedial nucleus of the thalamus at P15 and in the posterior medial nucleus at P30, when compared to control rats. Finally, we observed lower performance in GAERS versus controls, at both P15 and P30, in a whisker‐mediated behavioral task. Significance: Our data show that the functionality of wS1 cortex and thalamus is altered early during absence epileptogenesis in GAERS and then evolves before spike‐and‐wave discharges are fully expressed. They suggest that the development of the pathological circuit disturbs the physiological one and may be responsible for both the emergence of seizures and associated comorbidities.